Preoperative Elemental Diet before Laparoscopic Anterior Resection in Patients with Advanced Stenotic Rectal Cancer - Taketomi, Akinobu; Iijima, Hiroaki; Homma, Shigenori; Yoshida, Tadashi; Ichikawa, Nobuki (Journal of the Anus, Rectum and Colon, 2021)
Objectives: To evaluate the feasibility of our new preoperative enteral nutrition protocol using Elental® without mechanical bowel preparation (MBP) before laparoscopic anterior resection (LAR) in patients with advanced stenotic rectal cancer.Methods: Among 74 patients with advanced rectal cancer (clinical stages T3 and T4) scheduled to undergo LAR, 42 patients with stenotic rectal cancer were administered Elental® (900 kcal/day) without MBP before LAR (group S). Thirty-two patients without stenosis (group NS) did not receive preoperative nutritional support but underwent MBP.Results: Group S patients were maintained in a fasting state and received an elemental diet approximately 10 days preoperatively without severe adverse effects. The incidence of postoperative complications (Clavien-Dindo classification ≥ grade 2) was significantly lower in group S than that in group NS (adjusted odds ratio [OR]: 6.046, P = 0.008). Logistic regression analysis revealed that group NS exhibited higher risks of developing postoperative complications than those exhibited by group S (OR: 4.32, 95% confidence interval [CI]: 1.28-17.28, P = 0.018). Among preoperative characteristics, the clinical tumor stage indicated a significant intergroup difference. Thus, the clinical stage was selected as a covariate and adjusted in the logistic regression model to calculate a covariate-adjusted OR. Group NS exhibited a higher incidence of postoperative complications than group S (adjusted OR: 6.05, 95% CI: 1.58-28.35, P = 0.008).Conclusions: Administration of an elemental diet using Elental® without MBP before LAR is a feasible strategy in patients with advanced stenotic rectal cancer. Application of this research may encourage use of Elental® in the clinical setting.